Perceptual Spaces Induced by Cochlear Implant All-Polar Stimulation Mode - McKay, Colette; Marozeau, Jeremy (Sage Journals, 2016)
It has been argued that a main limitation of the cochlear implant is the spread of current induced by each electrode, which activates an inappropriately large range of sensory neurons. To reduce this spread, an alternative stimulation mode, the all-polar mode, was tested with five participants. It was designed to activate all the electrodes simultaneously with appropriate current levels and polarities to recruit narrower regions of auditory nerves at specific intracochlear electrode positions (denoted all-polar electrodes). In this study, the all-polar mode was compared with the current commercial stimulation mode: the monopolar mode. The participants were asked to judge the sound dissimilarity between pairs of two-electrode pulse-train stimuli that differed in the electrode positions and were presented in either monopolar or all-polar mode with pulses on the two electrodes presented either sequentially or simultaneously. The dissimilarity ratings were analyzed using a multidimensional scaling technique and three-dimensional stimulus perceptual spaces were produced. For all the conditions (mode and simultaneity), the first perceptual dimension was highly correlated with the position of the most apical activated electrode of the electrical stimulation and the second dimension with the position of the most basal electrode. In both sequential and simultaneous conditions, the monopolar and all-polar stimuli were significantly separated by a third dimension, which may indicate that all-polar stimuli have a perceptual quality that differs from monopolar stimuli. Overall, the results suggest that both modes might successfully represent spectral information in a sound processing strategy
Keywords: cochlear implant; all-polar stimulation; monopolar stimulation; multidimensional scaling